DO WE NEED MORE PRECISE METHODOLOGICAL RULES FOR WRITING REGULATIONS? - Ćorić, Dragana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2022)
In order for language to be fully accepted as a goal of communication, it is necessary that “participants have the same code, ie. a system of signs or symbols on the basis of which they compose messages. "Communication flows smoothly when all parties in the process know equally well the code  that is used in communication. Sometimes, the code used in the preparation of messages differ from the code known to other participants on the other side of  the communication process. Communication becomes fuzzy and one-way and must be brought to a state of unambiguous code used for both preparing and receiving messages. In the process of writing regulations, different language codes are used: the one known to everyone, that is, mostly known to everyone, and the other, which is composed of professional terms and terms from foreign languages. The terms from this second code must necessarily be explained by the terms from the first code,  that is better known and more frequently used code, since the regulations are also written for a wider circle of people, not only for lawyers who know the second code better.             Due to linguistic, but also structural and logical challenges that arise in the process of writing regulations, in 2010 the Unified Methodological Rules for Writing Regulations were adopted. This act regulated in the most precise way,  the way of writing regulations  so far, their internal structure,  and also insisted on determining a unique writing style and terminology that will be used when writing legal acts  because of the variety of addressees to which the regulations refer.            In our paper, we consider the possible need for change, ie even greater linguistic specification of some provisions of this regulation, in the context of the role and significance of language in law. All our proposals stem from the well-explained challenges that modern legislation has been facing lately in the process of its creation and self-application.
Keywords: language, methodological rules, regulations